Earth Air Tube Heat Exchanger Novel Way for Energy Saving (International Journal of Scientific Research in Science and Technology, 2024)
The demands of cooling energy & thermal comfort requirements are rapidly increasing day by day due to the global warming effect. The temperature of Tropical and Subtropical regions is as high as 50 ℃ in summer, and it is as low as below 10 ℃ in winter. So we may utilize the fact that the temperature of the earth at a depth of 2–3 m is constant throughout the year irrespective of the season, and that constant temperature is called earth undistributed temperature (EUT) so this may be utilized for heat rejection of air in the summer for cooling purpose (heat source) and heat addition of air in the winter for the heating purpose. The current setup is developed to explore the possibility of Earth Air Tube Heat Exchanger (EATHE) installation for heating and cooling in this region to curb the demand for energy Consumption. In the present research, a setup of Earth Air Tube Heat Exchanger (EATHE) is modelled in solid work and computational fluid dynamics software is used to analyse the performance of EATHE. The results are calculated by considering prominently two PVC and copper pipe materials, measurement of atmospheric temperature and inside temperature of soil at a depth of 6 feet in summer is done. Calculations of the amount of heat transfer and work input to the blower were done by applying suitable thermodynamic formulae and boundary condition. It has been found that a significant temperature drop has been found with the present Earth Air Tube Heat Exchanger (EATHE) modelled and proved to be very effective and novel technique which utilized geothermal energy to our advantage.